Two-Photon Microscopy with Diffractive Optical Elements and Spatial Light Modulators - Watson, Brendon O.; Nikolenko, Volodymyr; Araya, Roberto; Peterka, Darcy S.; Woodruff, Alan; Yuste, Rafael (Frontiers in Neuroscience, 2010)
Two-photon microscopy is often performed at slow frame rates, due to the need to serially scan all points in a field of view with a single laser beam. To overcome this problem, we have developed two optical methods that split and multiplex a laser beam across the sample. In the first method a diffractive optical element (DOE) generates a fixed number of beamlets that are scanned in parallel, resulting in a corresponding increase in speed, or in signal-to-noise ratio, in time-lapse measurements. The second method uses a computer-controlled spatial light modulator (SLM), to generate any arbitrary spatio-temporal light pattern. With an SLM one can image or photostimulate any predefined region of the image, such as neurons or dendritic spines. In addition, SLMs can be used to mimic a large number of optical transfer functions, including light path corrections or as adaptive optical devices.